CONTROL OF RADIOACTIVE SAFETY AND QUALITY OF MEDICINAL VEGETABLE RAW MATERIALS OF THE GREATER BURDOCK (ARCTIUM LAPPA L.) ROOTS IN VORONEZH REGION - N. A. Dyakova; A. I. Slivkin; S. P. Gaponov (Разработка и регистрация лекарственных средств)
Introduction. Radionuclides are recognized as one of the most dangerous pollutants of a surrounding medium in forces of their fissile migration on biological chains and influences on metabolism of alive organisms now.Aim. Studying of accumulation of radionuclides and polysaccharides in roots of a burdock big, collected in the territory of the Voronezh region in the areas which are influenced various anthropogenic influence and also an interrelation research between accumulation of these groups of substances.Materials and methods. The raw material was collected in the territory of Voronezh Region in the areas with different anthropogenic impact. Based on cartography the 36 points of the medicinal vegetable raw material samples collection were chosen in Voronezh Region. The subject matter was the roots of the Greater Burdocks as a wide spread perennial plant. The main artificial (Sr-90 and Cs-137) and natural (K-40, Th-232 and Ra-226) radionuclides as well as a concentration of the total amount of polysaccharides in terms of fructose and the total amount of gravimetrically determined polysaccharides were defined in the samples.Results and discussion. All the samples met the requirements of the pharmacoeial article of the artificial radionuclides content. A content of the total amount of polysaccharides in terms of fructose determined by spectrophotometry significantly varied in the root samples depends on their collection point. Thus, in protected reserved areas a content of the total amount of polysaccharides in term of fructose was 30-45 % high than in the samples from ecologically unfavourable areas. However all the samples also met the requirements of the pharmacoeial article of the total amount of polysaccharides in terms of fructose. A content of the polycaccharides close to the lower norm was found out in a sample collected in Povorino, while a content of the polycaccharides in terms of fructose significantly exceeded the normative standard in the rest of the samples. A content of gravimetrically determined water-soluble polysaccharides in the roots varied from 21,17 to 37,82 %. No noticeable anthropogenic effect on the accumulation of these substances was found. The samples from ecologically unfavourable and protected areas were little different from each other in a quantitative content of water-soluble polysaccharides.Conclusion. The correlation coefficients between the content of radionuclides and major groups of bioactive substances in the roots indicated that the radionuclides accumulated in the greater budock roots in a minor amounts and they did not affect the content of bioactive substances in plant raw material.